An Eigenfunction Expansion Method for EM Scattering by Arbitrary Shaped Multilayer Cylinders with Axially Biased Ferrite Layers - Aslanyurek, Birol; Gurbuz, Tolga Ulas (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2025)
Ferrites are widely used in microwave applications due to their anisotropic magnetic properties. In this study, we extend the method that we previously introduced for computing the electromagnetic fields scattered from arbitrary shaped multilayer cylinders with isotropic layers to those with axially biased ferrite layers. The method is basically an eigenfunction expansion procedure developed for noncircular scatterers. When the layers are isotropic, the method is used to solve only the ordinary wave equations. On the other hand, for ferrite layers, the solution of the extraordinary wave equation is required. Here, we derived the necessary expressions within the procedure for solving the extraordinary wave equation. Numerical simulations demonstrate that this extension of the method yields satisfactory results in a short computational time.
Keywords: Ferrites; Nonhomogeneous media; Propagation; Vectors; Eigenvalues and eigenfunctions; Numerical simulation; Mathematical models; Tensors; Magnetic properties; Magnetic fields; Eigenfunction expansion; electromagnetic scattering; multilayer objects; 2-DIMENSIONAL SCATTERING; SERIES SOLUTION; DESIGN; Engineering; Telecommunications